2015
DOI: 10.3892/etm.2015.2215
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium modulates the expression levels of calcification-associated factors to inhibit calcification in a time-dependent manner

Abstract: Vascular calcification, a common complication in patients with chronic kidney disease, involves a variety of mechanisms associated with the regulation of calcification-associated factors. Previous clinical studies have indicated that magnesium is involved in the reduction of vascular calcification; however, the mechanism underlying this process remains unknown. The aim of the present study was to investigate the effects of magnesium on β-glycerophosphate (β-GP)-induced calcification and the underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…Several other studies have demonstrated an association between lower serum Mg and mortality among dialysis patients [21, 22, 24–27] This association could potentially be attributable to low serum Mg causing accelerated vascular calcification. Increasing data from in-vitro and animal studies support the assertion that Mg acts as an inhibitor of vascular calcification [612]. The addition of Mg to vascular smooth muscle cells increases the expression of anti-calcification proteins, such as matrix G1a, bone morphogenetic protein-7 and osteopontin, and inhibits an osteoblastic transformation [7, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have demonstrated an association between lower serum Mg and mortality among dialysis patients [21, 22, 24–27] This association could potentially be attributable to low serum Mg causing accelerated vascular calcification. Increasing data from in-vitro and animal studies support the assertion that Mg acts as an inhibitor of vascular calcification [612]. The addition of Mg to vascular smooth muscle cells increases the expression of anti-calcification proteins, such as matrix G1a, bone morphogenetic protein-7 and osteopontin, and inhibits an osteoblastic transformation [7, 11].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been comparatively little exploration of the association of serum magnesium (Mg) with vascular calcification. Both in-vitro and animal studies have found that the addition of Mg to vascular smooth muscle cells inhibits the increase in mineralization associated with an osteoblastic phenotype, increases the expression of anti-calcification proteins, and down regulates pathways necessary for the development of vascular calcification [612]. The transient receptor potential melastin (TRPM)7 cation channel as well as the Wnt/β-catenin pathway are proposed as being essential to Mg regulating vascular calcification [7, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium plays an important role in vascular health, with normal magnesium homeostasis in VSMC maintained via TRPM7 cation channels. Magnesium prevents posttranscriptional changes in VSMC differentiation and apoptosis and up‐regulates VC inhibitors (MGP and osteopontin), whilst counteracting expression of osteogenic transcription factors (BMP‐2, RUNX2, Msh homeobox 2, and SRY‐ box 9), bone proteins and genes associated with matrix mineralization (osteocalcin and TNAP) . In animal models of VC, dietary supplementation with magnesium results in marked reduction in VC and mortality, improved mineral metabolism, including lowering of PTH, as well as improvement in renal function …”
Section: Future Potential Management For Vc In Clinical Evaluationmentioning
confidence: 99%
“…12 Both in-vitro and animal studies have found that the Mg addition to vascular smooth muscle cells inhibits the increase in mineralization associated with increase in expression of anticalcification proteins, and down regulates pathways necessary for the development of vascular calcification. [13][14][15][16][17][18][19] A study has demonstrated that a higher serum Mg significantly decreased the mortality risk in haemodialysis patients and lower serum Mg level has been found to be associated with increased mortality in them. [20][21][22][23] In the present study, a cross sectional study has been conducted to characterize the relationship between Mg level and vascular calcification.…”
Section: Introductionmentioning
confidence: 99%